The Relationship Between Cross-Program and Cross-Sectoral Support and the Achievement of Nutrition Programs in Stunting Reduction - Harris Rambey (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Stunting remains a major public health challenge in Indonesia. One of the factors influencing the success of nutrition programs for stunting prevention is cross-program and cross-sectoral support, which significantly affects intervention effectiveness at the primary healthcare level. Objective: This study aimed to analyze the relationship between cross-program and cross-sectoral support and the achievement of nutrition programs for stunting prevention at Batang Kuis Health Center, Deli Serdang Regency. Research Methods: A quantitative approach with a descriptive analytic design was employed. A total of 50 respondents, including health workers, health cadres, and representatives from education and social sectors, were selected through purposive sampling. Data were collected using questionnaires and in-depth interviews and analyzed with Pearson correlation and chi-square tests. Results: The study revealed a significant relationship between cross-program and cross-sectoral support and nutrition program achievements (p=0.003; r=0.65). Sector coordination, budget allocation, and monitoring were found to be suboptimal, contributing to an increase in stunting prevalence from 12.5% to 14.3% in 2022. Conclusion: Cross-sectoral and cross-program support plays a crucial role in the success of nutrition programs to combat stunting. Strengthening sectoral coordination, increasing nutrition program budgets, and empowering communities are recommended to accelerate stunting reduction efforts.